Hubungan Faktor Sosial Ekonomi Dengan Konsumsi Sayur-Sayuran Di Kecamatan Amuntai Tengah Kabupaten Hulu Sungai Utara - Heni Heni (LPPM Sekolah Tinggi Ilmu Pertanian Amuntai, 2019)
The high and low level of vegetable consumption is estimated to be influenced by several factors including income, price, education, number of family members, age and area of origin of housewives. This research aims to find out (i) the amount of vegetable consumption by housewives in Amuntai Tengah District, (ii) the amount of expenditure for vegetable consumption by households in Central Amuntai Subdistrict (iii) how much socio-economic factors affect the amount of vegetable consumption -Vegetables by households in Central Amuntai District. The study was conducted in 9 villages in Amuntai Tengah District, Hulu Sungai Utara Regency in April-May 2010. Using multistage random sampling, primary data was obtained from interviews and secondary data was obtained from the relevant agencies. The results showed that the average consumption of vegetables by households in Amuntai Tengah District was 8.57 kg / month with an expenditure of Rp. 57,706, 30 or 5.95 of total family income. From the correlation analysis and t test there is a significant relationship between the level of consumption of vegetables with family income, price and formal education level of housewives. The age factor of a housewife, the number of family members and the area of origin of a housewife do not have a significant relationship to the consumption of vegetables.